Adult-Onset Gitelman Syndrome: Case Analysis and Literature Review - Intissar Haddiya; Sara Ramdani; Aymane Kadi; Imane Machmachi; Mohammed Benabdelhak; Yassamine Bentata (Case Reports in Medicine)
Conclusion: The clinical and biochemical findings in these patients are strongly indicative of Gitelman syndrome, even in the absence of genetic confirmation. This study emphasizes the necessity of a multidisciplinary approach in diagnosing and managing Gitelman syndrome, where biochemical assessments and clinical findings are instrumental. While genetic testing could provide conclusive evidence, effective management through electrolyte supplementation plays a crucial role in improving patients’ quality of life.